Immunomodulatory effect of extracellular vesicles from Entamoeba histolytica trophozoites: Regulation of NETs and respiratory burst during confrontation with human neutrophils - Díaz-Godínez, César; Ríos-Valencia, Diana G.; García-Aguirre, Samuel; Martínez-Calvillo, Santiago; Carrero, Julio César (Frontiers in Cellular and Infection Microbiology, 2022)
Parasites release extracellular vesicles (EVs) which, in some cases, that modulate the host's immune response contributing to the establishment of the infection. In this work we have isolated and characterized the EVs released by trophozoites of the human protozoan parasite Entamoeba histolytica, the causal agent of amoebiasis, when alone or in coculture with human neutrophils, and determined their effect on neutrophil NETs and ROS production. Nanoparticle tracking analysis showed that amoebic EVs are variable in size, ranging from less than 50 nm to nearly 600 nm in diameter (average of 167 nm), whereas neutrophil EVs are more uniform in size, with an average of 136 nm. In cocultures amoeba:neutrophil (1:100) most EVs are 98 nm in size, which is the typical size of exosomes. EVs from amoebae and neutrophils showed almost equal levels of ROS, which were considerably increased in EVs from cocultures. Uptake of amoebic EVs by neutrophils was demonstrated by fluorescence and resulted in a significant reduction in the oxidative burst and NET release triggered by PMA, ionophore A23187, or the amoebae itself used as stimuli. Interestingly, uptake of EVs from cocultures did not affect ROS production, but instead caused a greater delay in the onset of NETs release and in their quantity. A comparative proteomic analysis between the EVs of amoebae and neutrophils separately vs. the cocultures showed a similar distribution of protein categories in the GO analysis, but differences in the expression and abundance of proteins such as cysteine proteases and the N-acetyl-D-galactosamine (GalNAc) inhibitable surface lectin and calreticulin galactose-affinity lectin in amoeba EVs, and various antimicrobial molecules in neutrophil EVs, such as lactotransferrin and myeloperoxidase. These results highlight the importance of EVs in the immunomodulatory effects exerted by amoeba on human neutrophils.